Fargo: Seeing the significance of style in television poetics?. (September 2019) - Sexton, Max; Lees, Dominic
This article explores the adaptation of the original film to television and how a strain of art or independent cinema contributed to the development of the first series of Fargo (2014–present). By making this comparison, the transition to television of the storyworld established by the Coen brothers raises questions about who is talking in the TV drama – the Coens or makers of the series. At the same time, Fargo can be more easily explained and understood as a strategy by writers, directors and producers that further complicate ideas to do with Noah Hawley, as its showrunner and the show's single-author status. In Fargo, fidelity to the Coen brothers as a testament to the memory of the original film is set against questions about the reliability of storytelling using complex imagery. By alternating between different levels of narration signified by its stylistic tonal qualities, Fargo succeeds in producing multiple meanings, representations and effects that call attention to textual pleasures in the complex television series.